Ingraining goal orientation behavior among Malaysian adolescents using Solution-focused group work (SFGW) - Shunmugam, Ratnadevi R; Noah, Sidek Mohd.; Jaafar, Wan Marzuki Wan (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2019)
Setting goals can be reviewed as aspirations for future betterment especially among adolescents. Goal-setting process involves aspects like future planning, principles, values, priorities, application of knowledge and decision making. This process varies according to individual needs and requires different approaches and guidance. Literature review prevailed that the essential ingredient of Solution-focused approach is setting goals. Solution-focused techniques found to be vital and crucial in assisting adolescents to set goals. Two objectives were drawn through literature reviews. Objective one is to determine the effectiveness of SFGW in increasing adolescent’s goal orientation behavior mean score between pre-test, post-test and follow-up test. And, the second objective is to compare the effects between SFGW intervention module (treatment group) and traditional module (control group) on goal orientation mean score for post-test and follow-up test. This is a true experimental with pre-test and post-test design using Solution-focused module and administration of questionnaires for data collection. A total of 66 samples who met the inclusion requirement were assigned randomly to experimental (n = 32) and control (n = 34) groups using paired-matched design. The samples in experimental group were given treatment using the SFGW intervention program for seven weeks. After the completion of the treatment, posttest and follow-up test were carried out and data was collected using Goal Orientation Scale. The collected data was analyzed using descriptive statistics, independent samples t-test, and one-way repeated measure ANOVA. The study discloses that SFGW does significantly affect the level of goal orientation behavior among Malaysian adolescents.